POKOK BAHASAN PENDIDIKAN AGAMA ISLAM DI MADRASAH: PERBANDINGAN KURIKULUM TINGKAT SATUAN (KTSP) DAN KURIKULUM 2013 (K-13) - Rosiddin Harahap (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2017)
The Education Unit Level Curriculum (KTSP) is an idea of development that is placed in the position closest to learning, namely schools and educational units. KTSP is a manifestation of education reform that gives autonomy to schools and educational units to develop curriculum in accordance with their respective potentials, demands and needs. Whereas the 2013 Curriculum aims to encourage students or students to be able to better observe, ask, reason, and communicate (present) what they have acquired or know after receiving the subject matter.